2017
DOI: 10.3389/fpls.2017.00912
|View full text |Cite
|
Sign up to set email alerts
|

Rational Water and Nitrogen Management Improves Root Growth, Increases Yield and Maintains Water Use Efficiency of Cotton under Mulch Drip Irrigation

Abstract: There is a need to optimize water-nitrogen (N) applications to increase seed cotton yield and water use efficiency (WUE) under a mulch drip irrigation system. This study evaluated the effects of four water regimes [moderate drip irrigation from the third-leaf to the boll-opening stage (W1), deficit drip irrigation from the third-leaf to the flowering stage and sufficient drip irrigation thereafter (W2), pre-sowing and moderate drip irrigation from the third-leaf to the boll-opening stage (W3), pre-sowing and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 42 publications
4
52
1
Order By: Relevance
“…Soil-Water Content. Because drip irrigation is a type of partial irrigation, the area under the dripper is humid during irrigation; after irrigation, soil moisture is changed by many factors, such as the crop root system, atmospheric evaporation, self-gravity, and the influence of film mulching, which makes the conditions in the surrounding soil more complex and causes soil moisture to have both temporal and spatial distribution patterns [36]. The spatial and temporal distribution of soil moisture is not homogeneous (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Soil-Water Content. Because drip irrigation is a type of partial irrigation, the area under the dripper is humid during irrigation; after irrigation, soil moisture is changed by many factors, such as the crop root system, atmospheric evaporation, self-gravity, and the influence of film mulching, which makes the conditions in the surrounding soil more complex and causes soil moisture to have both temporal and spatial distribution patterns [36]. The spatial and temporal distribution of soil moisture is not homogeneous (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…This finding indicated that relatively low soil water contents are not good for growth and development of the aboveground parts during the vegetative growth stage. These adverse effects may involve physiological responses [55], leaf area expansion [48], root growth [56] resulting in a decreased plant VOB to reproductive biomass and ultimately reduced yield [11]. Luxury, vegetative growth can consume excessive amount of nutrients and increases competition between vegetative and reproductive growth and consequently fruit shedding [57].…”
Section: Discussionmentioning
confidence: 99%
“…Plant roots respond to the variation in surface soil moisture e.g. water deficit in the upper soil profile leads to deeper root penetration, while excess water in the upper layer reduces root penetration [ 33 ], i.e. up to 3 m.…”
Section: Root Growthmentioning
confidence: 99%